Review of the hemp-based brick that purifies air pollution, reduces humidity and is a thermal insulator: An innovative solution to reduce environmental pollution in the construction industry - Revatta Alvites, Katherine (2023)
In the construction industry there are several problems that negatively impact the environment from the process of obtaining materials, the construction of buildings and their use. That is why the bibliographic review research analyzes the use and application of the hemp-based brick with the support of the Scopus database and the VOSviewer software as data analytics, the characteristics of the brick were taken into account as well As an air pollution purifier, humidity reduction and thermal insulation, graphs related to these characteristics were obtained, highlighting the words with the highest frequency in the research, countries that published and bibliometric maps worldwide. The results help us determine that there is an application of this brick in countries with the greatest needs and growth and also in potential countries, however we believe that in Peru there is no analysis or interest in this brick. This hemp-based brick has positive advantages for the environment and is potentially ecological from the beginning of obtaining the materials, used in the construction of houses and then as waste, in these three phases it contributes to the environment. The purpose of the research is to be the beginning for future investments and research related to the hemp-based brick applied in the construction industry and the other objective is to motivate professionals to use and apply this brick that will have benefits for the environment.